Pengaruh Kualitas Produk, Kualitas Layanan, dan Emosional terhadap Kepuasan Pelanggan Sogo Departemen Store - Prandita, Luli; Iriani, Sri Setyo (BISMA (Bisnis dan Manajemen), 2018)
This research was conducted to examine the effect of product quality, service quality, and emotional, and costumer satisfaction. The objective of research to know the influence of product quality, service quality, emotional toward costumer satisfaction on Sogo Departmen Store. This study used a accidental sampling by the number of 110 respondens by using causal research. The analysis used is multiple regression analysis by using SPSS 16 in seeing the independent variables influence the dependent variable either jointly or individually. The results showed that product quality, service quality, emotional significantly influence toward costumer satisfaction either jointly or individually